Determinants of agricultural protection from an international perspective: The role of political institutions - Henning, Christian (International Food Policy Research Institute, 2008)
This paper explores the role of political institutions in determining the ability of agriculture to avoid taxation in developing countries or attract government transfers in industrialized countries. The utilized model is based on a probabilistic voting environment, wherein rural districts are less ideologically committed than urban districts in industrialized countries, and the reverse is true in developing countries. As a consequence, in industrialized (developing) countries rural (urban) districts are pivotal in determining the coalition that obtains a majority, whereas urban (rural) districts are pivotal within the majority itself. In bargaining at the level of the legislature, this generates a conflict between a government that tends to favor rural (urban) districts, and a parliamentary majority that is dominated by urban (rural) concerns. As district size grows and the electoral system converges to a purely proportional system, both of these biases are attenuated. Overall, we see opposing nonlinear relationships between district size and agricultural subsidies on the one hand and district size and taxation on the other. In developing countries, taxation of agriculture first increases and then decreases with district magnitude; in industrialized countries, agricultural subsidization first increases and then decreases with district magnitude. Moreover, the impact of district magnitude on the level of agricultural subsidization is attenuated in presidential versus parliamentary systems, while the level of agricultural taxation is amplified in presidential systems. In the present paper, these findings are first theorized and then empirically confirmed by a cross-country analysis of data from 37 countries over a 20-year period.